Symmetries of th-Order Approximate Stochastic Ordinary Differential Equations - E. Fredericks; F. M. Mahomed (Journal of Applied Mathematics)
Symmetries of th-order approximate stochastic ordinary differential equations (SODEs) are studied. The determining equations of these SODEs are derived in an Itô calculus context. These determining equations are not stochastic in nature. SODEs are normally used to model nature (e.g., earthquakes) or for testing the safety and reliability of models in construction engineering when looking at the impact of random perturbations.